Vegetable milks and their fermented derivative products - Neus Bernat; Maite Cháfer; Amparo Chiralt; Chelo González-Martínez (International Journal of Food Studies)
The so-called vegetable milks are in the spotlight thanks to their lactose-free, animal protein-free and cholesterol-free features which fit well with the current demand for healthy food products. Nevertheless, and with the exception of soya, little information is available about these types of milks and their derivatives. The aims of this review, therefore, are to: highlight the main nutritional benefits of the nut and cereal vegetable milks available on the market, fermented or not; describe the basic processing steps involved in their manufacturing process; and analyze the major problems affecting their overall quality, together with the current feasible solutions. On the basis of the information gathered, vegetable milks and their derivatives have excellent nutritional properties which provide them a high potential and positive market expectation. Nevertheless, optimal processing conditions for each raw material or the application of new technologies have to be researched in order to improve the quality of the products. Hence, further studies need to be developed to ensure the physical stability of the products throughout their whole shelf-life. These studies would also allow for a reduction in the amount of additives (hydrocolloids and/or emulsifiers) and thus reduce the cost of the products. In the particular case of fermented products, the use of starters which are able to both improve the quality (by synthesizing enhanced flavors and providing optimal textures) and exert health benefits for consumers (i.e. probiotics) is the main challenge to be faced in future studies.